Pathways to Careers in Healthcare - Hong, Philip Young P., 1972-; King, Christopher T. (Book collections on Project MUSE., 2019)
"The authors in this book present findings, lessons, and recommendations that emanated from HPOG research and evaluations for consideration by policymakers, program operators, and other researchers"--